Republic of Latvia : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Latvia during 1994-96. The paper highlights that developments during this period have been dominated by the after-effects of the fiscal slippage in 1994 and the banking crisis in 1995, although there are signs of a recovery from these adverse episodes. The paper provides an in-depth analysis of selected economic issues facing Latvia. It analyzes the environment for the private-sector development, and reviews interest rate developments, focusing in particular on the treasury-bill market.